Insulin and C-peptid responses to oral glucose tolerance test in patients with idiopathic hepatosteatosis - Muhsin KAYA; Ali Reşit BEYLER; Murat Faik ERDOĞAN (Turkish Journal of Gastroenterology, 2019)
-